Rural destination revitalization in China: applying evolutionary economic geography in tourism governance. Issue 2 (1st February 2021) - Deng, Aimin; Lu, Junyang; Zhao, Zhengyuan
ABSTRACT: Tourism is considered a way to mitigate adjustments in the regional industrial structure. Three cases in this study illustrate the importance of initial conditions and how stakeholder collaboration can mitigate these deficiencies. We proposed a new model for rural destinations in different phases, and concluded that by addressing the needs of tourists and providing proper products, path innovation can be advanced. Study results also showed that creating a more inclusive culture advances innovation and the sustainable development of the region. This requires the participation of local communities to jointly advance path innovation.